Fabrication of glucose sensor using graphene - Soo Ling, Chong (2015)
Graphene is a one-atom-thick allotrope of carbon. Due to its unique mechanical and electronic properties, graphene has been touted as very promising material for a great number of applications. In particular, biosensor is a device for the detection of specific analyte which combines a biological compound with a physicochemical detector component. There are three major components that complete a biosensor, namely the sensitive biological element, the transducer or detector element and also the associated electronics or signal processors. The working principle of graphene-based enzymatic electrodes is based on the direct electrochemistry of enzymes whereby electron transfer occurs between the electrode and the active centre of the enzymes without the participation of any mediators or reagents. In the current work, a graphene based glucose biosensor was prepared. The reduced graphene oxide (RGO)-glucose oxidase (GOx) was prepared from graphite powder as starting material. Material synthesis involved pre-oxidation of graphite to graphite oxide followed by further oxidation to graphene oxide. Subsequently, hydrazine monohydrate was used to reduce the graphene oxide to reduced graphene oxide. Finally, glassy carbon electrode (GCE) /RGO-GOx based glucose sensor was fabricated. Thereafter, the sample was tested with different concentrations of glucose solution. It was also being subjected to ultraviolet-visible absorption spectrophotometry (UV-Vis), Fourier transform infrared spectroscopy (FTIR) and cyclic voltammetry (CV). From this study, the obtained results are allowed for assessment of an optimum and sensitivity of the GCE/RGO-GOx based glucose biosensor towards the glucose concentration. It can be concluded that GCE/RGO-GOx based glucose biosensor can detect circa 3 to 7 mM glucose.